Optimizing Slow Learners’ Understanding through Environment-Based Manipulative Media on the Number Operation Topic - Jannah, Ukhti Raudhatul; Sholihah, Wildanus; Basri, Hasan; Dewi, Nindian Puspa; Rahmad, Rahmad; Hafsi, Ainur Rofiq (FKIP Universitas Lampung, 2025)
Every individual, including students with special needs such as slow learners, has the right to receive equal education. The current study aimed to examine elementary slow learners’ understanding of number operation concepts through the use of manipulative media drawn from their local environment at Pademawu Barat 1 Elementary School, Pamekasan. A qualitative case study design was employed, involving two fifth-grade students identified as slow learners through a diagnostic test, the Colored Progressive Matrices (CPM) psychological assessment, questionnaires, and interviews. Data were collected through formative and summative assessments, classroom observations, and video documentation, then analyzed descriptively and qualitatively, with validation ensured through source triangulation. An individualized learning intervention was conducted using manipulative media such as ice cream sticks and shell boards that were relevant to the students’ coastal environment. The findings revealed that the use of manipulative media combined with structured scaffolding gradually improved students’ understanding of number operations, particularly in addition, subtraction, and multiplication. This approach not only helped to concretize abstract mathematical concepts but also enhanced the engagement, independence, and motivation of students who are slow learners. The learning environment became more positive and interactive, fostering greater student participation. In conclusion, this study highlights the importance of incorporating environment-based manipulative media and providing tailored scaffolding to support inclusive mathematics learning in elementary schools, particularly in resource-limited contexts. The findings may serve as a reference for educational development in Indonesia, underscoring the need for educators and policymakers to design adaptive and equitable learning strategies that meet the diverse needs of all students. Keywords: conceptual understanding, number operations, manipulative media, slow learners, inclusive education.